PEMANFAATAN SELULOSA POPOK BAYI SEBAGAI SUBSTRAT UNTUK PRODUKSI ENZIM SELULASE OLEH ISOLAT BAKTERI S-16 DAN S-22 STRAIN LOKAL RIAU - Dahlena, Maya; Dahliaty, Andi; Sy, Silvera Devi (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The S-16 and S-22 cellulolytic bacteria isolated from Siak River water were used in this study to produce cellulase with disposable diapers as a substrate. Cotton is the main component in the disposable diapers that can be used as a substrate in the production of cellulase. Cellulase is an enzyme that catalyzes the hidrolisis of β-1-4-glycosidic bond of cellulose. Fermentation was carried out for 10, 20, and 30 days by S-16 and S-22. Enzyme activity was determined using Nelson-Somogyi method. The results showed that the highest enzyme activity obtained at 20 days, with S-16 of (2,654 ± 0,53)x 10 U/mL and S-22 of (13,704 ± 4,91)x 10-3 U/mL.